Chiral Microneedles from an Achiral Bis(boron dipyrromethene): Spontaneous Mirror Symmetry Breaking Leading to a Promising Photoluminescent Organic Material - Gartzia-Rivero, Leire; Ray Leiva, César; Sánchez-Carnerero, Esther M; Bañuelos, Jorge; Moreno, Florencio; Maroto, Beatriz L; García-Moreno, Inmaculada; Infantes, Lourdes; Mendez, Bianchi; López-Arbeloa, Iñigo; de la Moya, Santiago (Langmuir, 2019)
Supramolecular self-assembly of a highly flexible and achiral meso bis(boron dipyrromethene) [bis(BODIPY)] dye straightforwardly yields fluorescent microfibers, exhibiting an intriguing anisotropic photonic behavior. This performance includes the generation of chiroptical activity owing to spontaneous mirror symmetry breaking (SMSB). Repetition of several self-assembly experiments demonstrates that the involved SMSB is not stochastic but quasi deterministic in the direction of the induced chiral asymmetry. The origin of these intriguing (chiro)photonic properties is revealed by fluorescent microspectroscopy studies of individual micrometric objects, combined with X-ray diffraction elucidation of microcrystals. Such a study demonstrates that J-like excitonic coupling between bis(BODIPY) units plays a fundamental role in their supramolecular organization, leading to axial chirality. Interestingly, the photonic behavior of the obtained fibers is ruled by inherent nonradiative pathways from the involved push-pull chromophores, and mainly by the complex excitonic interactions induced by their anisotropic supramolecular organization.